The Effect of Implementing PJBL-Based E-Learning in the Independent Curriculum in Improving Science Literacy - Ewisahrani, Ewisahrani; Nursaban, Eva (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2025)
The curriculum of STKIP Harapan Bima establishes the course Science Learning in Elementary Schools, with a lecture duration of 60 minutes per course. Such a limited time demands the achievement of indicators: students are able to explain, apply, and analyze material related to science learning. The use of textbooks or e-books does not always succeed in encouraging students to gain prior understanding before starting class sessions. Students rarely read the provided materials. Some of them struggle to grasp the meaning of the content. In fact, many students do not even open the files given. As a result, they lack prior understanding when beginning classroom learning. The main objective of this study is to determine the effect of implementing E-Learning based on Project-Based Learning (PjBL) to improve scientific literacy skills. The method used in this research is a quasi-experimental method. A quasi-experimental method is a research method in which the implementation does not use random assignment, but rather utilizes existing groups. The learning provided had a positive, significant, and equitable impact on student learning outcomes. The large average increase, the improvement of minimum scores eliminating low-achieving students, and the consistency of score distribution indicate that learning objectives were effectively achieved. Based on the results of the Kolmogorov-Smirnov and Shapiro-Wilk tests, it can be concluded that the research data were normally distributed (p > 0.05). From Levene’s Test, it can be concluded that the pretest and posttest scores had homogeneous variances (p > 0.05). This strengthens the validity of using parametric tests in analyzing the differences in students’ learning outcomes before and after the learning treatment. The results of the paired t-test indicate that there is a significant difference between pretest and posttest scores (t = 38.1054; p < 0.05). This proves that the applied learning treatment or method was effective in improving students’ learning outcomes. The use of e-learning based on Project-Based Learning (PjBL) was proven effective with an average score achievement of 80.88. This demonstrates that the learning model was able to significantly enhance students’ learning outcomes while also supporting the mastery of 21st-century competencies such as critical thinking, collaboration, and problem-solving.